GREEN SYNTHESIS OF SILVER AND GOLD NANOPARTICLES USING TRADESCANTIA PALLIDA EXTRACT: THEIR CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY - Ahmed, Naseer; Kamran Mehdi; Saqib Khan; Abbas Ali; Khandil Badshah (PROCEEDING AL GHAZALI International Conference, 2023)
The purpose of this research was to find eco-friendly nanoparticles synthesized from the leaf extract of Tradescantia pallida and to find their antimicrobial activities. Phytochemical investigation of these plants reveals the occurrence of flavonoids, alkaloids, sterols, terpenoids, tannins, saponins, proteins, carbohydrates phenols, etc. Nanoparticle confirmation was done by UV/Visible spectroscopy which gives a peak at 429 nm for Ag-NPs and 532 nm for Au-NPs. The morphology of the nanoparticle was checked by spectroscopic techniques. The average size of the nanoparticles was established by using SEM analysis. The antibacterial activity of synthesized nanoparticles was checked against gram-positive and gram-negative bacterial strains like Escherichia coli, Staphylococcus aureus, Salmonella typhimurium, and Pseudomonas aeruginosa and for antifungal activity two fungal strain Candida albicans and Aspergillus niger were used. The results demonstrate that the synthesized nanoparticles have promising activity against all used strains and can be used as antimicrobial agents.